Exploration and Identification of Trichoderma sp. with Baiting Method as a Biological Agent in Horticultural Lands - Firdaus, Emilda Zahrotul; Indahsari, Wiwin Misnati Nur Indahsari; Bahri, Saiful; Tyastirin, Esti (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2024)
The use of biological agents is an effective way to prevent the negative impacts of excessive synthetic chemical pesticide use. Trichoderma sp., a saprophytic fungus, acts as a biocontrol agent against various phytopathogenic molds and is more commonly found in rooted soil and leaves than in stems or fruits. This study aims to identify the characteristics and presence of Trichoderma sp. in horticultural land using the baiting method. Isolation was carried out by collecting fungi grown on rice, corn, and coconut bait using an inoculation needle. Three Trichoderma sp. isolates were obtained from chili and bamboo root soil using rice and corn bait. The results showed that the three isolates had similar characteristics: colonies were dark green, circular in shape, powdery in texture, and had entire margins. Microscopically, the isolates featured branched and upright conidiophores arranged vertically, short and thick phialides, round greenish conidia, and septate hyphae resembling threads.